2020
DOI: 10.1097/mca.0000000000000966
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding the emergence of contrast-induced acute kidney injury in acute coronary syndrome: routine hydration treatment

Abstract: Background: Patients with acute coronary syndrome (ACS) have about a three-fold risk for developing contrast-induced acute kidney injury(CI-AKI). Investigating studies on routine hydration therapy have frequently included patients with stable coronary artery disease and high risk of CI-AKI [estimated glomerular filtration rate (eGFR) < 60 ml/min]. However, data on routine hydration treatment in non-ST segment elevation myocardial infarction (NSTEMI) patients with eGFR ≥60 ml/min are insufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, contrast media administration during angiography and PCI can increase the risk of contrast-induced acute kidney injury, an impairment of renal function reported in up to 10% of cardiac catheterization and PCI patients [145,147]. Patients with ACS have about a three-fold risk of developing contrast-induced acute kidney injury versus those without ACS [148]. This impairment is associated with short-and long-term mortality and MACE [149,150].…”
Section: Additional Challenges-technology Risksmentioning
confidence: 99%
“…Furthermore, contrast media administration during angiography and PCI can increase the risk of contrast-induced acute kidney injury, an impairment of renal function reported in up to 10% of cardiac catheterization and PCI patients [145,147]. Patients with ACS have about a three-fold risk of developing contrast-induced acute kidney injury versus those without ACS [148]. This impairment is associated with short-and long-term mortality and MACE [149,150].…”
Section: Additional Challenges-technology Risksmentioning
confidence: 99%
“…Acute ST-segment elevation myocardial infarction (SETMI) is an important form of coronary atherosclerosis and is the primary cause of death in people with coronary heart disease. The emergency percutaneous coronary intervention has been developing in recent years, and breakthroughs have been made for the treatment of acute SETMI, which has largely reduced its disability and fatality rates [5][6] Percutaneous coronary intervention is one of the effective methods of clinical treatment of myocardial infarction at present, but there is also the risk of coronary artery restenosis and ischemia after the operation. At present, after carrying out PCI, clinicians usually ask post-PCI patients to rest in bed for two days before they can start their activities as a way to better help the post-PCI patients recover their health [11][12].…”
Section: Review Of Relevant Research Workmentioning
confidence: 99%
“…38 , 39 In recent studies, hydration therapy has also been shown to reduce the incidence of CA-AKI in patients with eGFR≥60 mL/min/1.73 m 2 . 40 However, excessive transfusion may increase the risk of heart failure, arrhythmia and short-term death in high-risk patients. 41 Therefore, the implementation of hydration therapy should be guided according to the central venous pressure (CVP), left ventricular end diastolic pressure (LVEDP), bioimpedance and urine volume.…”
Section: Prophylaxis and Treatment Of Ca-akimentioning
confidence: 99%